Reckoning technique of passenger airplane approach procedure in case of all main engines failure - M. A. Kiselev; S. V. Levitsky; V. A. Podobedov (Научный вестник МГТУ ГА)
Cases of failure (shutdown) of all the main engines of a multi-engine powerplant in flight, unfortunately, occur both in Russia and abroad. The causes of such situations may be, for example, a flying in volcanic ash cloud, as in the case of the incident with Boeing 747 over the island of Java in 1982, or the cessation of fuel supply, as in the cases of an emergency landing of Boeing 767-233 in 1983 on an unused military airfield Gimlii and Tupolev-204 in Omsk in 2002. At the same time, in the management documentation, the crew’s actions for this case are either not prescribed at all, or spelt out so concisely that they do not imply a specific list of actions, or, in other words, they require the crew to search for the necessary aircraft control actions within the circumstances of time shortage and increased stress levels. The proposed article reveals the content of the methodology that provides for the withdrawal of an aircraft with an inoperative power plant in a safe landing environment at every airfield with an outer marker. A distinctive feature of the considered approach is the absence of the need to bind the parameters of aircraft movement to explicitly stated landmarks. In addition, this approach is simple to implement and at the present stage of development of automatic control systems may well be implemented on board an aircraft in an automatic or director mode. The minimum information required for the calculation of the landing approach is limited to three parameters: the minimum drag airspeed in the landing configuration, the height of the flight over an outer marker before the landing and the height loss on turn spiral on the prelanding manoeuvre. The content of the method in the article is illustrated by the results of the calculation of landing in case of failure of both engines of the power plant for the prospective domestic short-medium-range aircraft MS-21.